Air quality improvement during triple-lockdown in the coastal city of Kannur, Kerala to combat Covid-19 transmission - C.T. Resmi; T. Nishanth; M.K. Satheesh Kumar; M.G. Manoj; M. Balachandramohan; K.T. Valsaraj (PeerJ, 2020)
The novel SARS-CoV-2 coronavirus that emerged in the city of Wuhan, China, last year has since become the COVID-19 pandemic across all continents. To restrict the spread of the virus pandemic, the Government of India imposed a lockdown from 25 March 2020. In India, Kannur district was identified as the first “hotspot” of virus transmission and a “triple-lockdown” was implemented for a span of twenty days from 20 April 2020. This article highlights the variations of surface O3, NO, NO2, CO, SO2, NH3, VOC’s, PM10, PM2.5 and meteorological parameters at the time of pre-lockdown, lockdown and triple-lockdown days at Kannur town in south India using ground-based analyzers. From pre-lockdown days to triple-lockdown days, surface O3 concentration was found to increase by 22% in this VOC limited environment. NO and NO2 concentrations were decreased by 61% and 71% respectively. The concentration of PM10 and PM2.5 were observed to decline significantly by 61% and 53% respectively. Reduction in PM10 during lockdown and triple-lockdown days enhanced the intensity of solar radiation reaching the lower troposphere, and increased air temperature and reduced the relative humidity. Owing to this, surface O3 production over Kannur was found to have increased during triple-lockdown days. The concentration of CO (67%), VOCs (61%), SO2 (62%) and NH3 (16%) were found to decrease significantly from pre-lockdown days to triple-lockdown days. The air quality index revealed that the air quality at the observational site was clean during the lockdown.